Shaping of the autoreactive T-cell repertoire by a splice variant of self protein expressed in thymic epithelial cells - Klein, Ludger; Klugmann, Matthias; Nave, Klaus-Armin; Kyewski, Bruno (Nature medicine, 2000)
Intrathymic expression of tissue-specific self antigens may be involved in immunological tolerance and protection from autoimmune disease. We have analyzed the role of T-cell tolerance to proteolipid protein (PLP), the main protein of the myelin sheath, in susceptibility to experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis. Intrathymic expression of PLP was largely restricted to the shorter splice variant, DM20. Expression of DM20 by thymic epithelium was sufficient to confer T-cell tolerance to all epitopes of PLP in EAE-resistant C57BL/6 mice. In contrast, the major T-cell epitope in SJL/J mice was only encoded by the central nervous system-specific exon of PLP, but not by thymic DM20. Thus, lack of tolerance to this epitope offers an explanation for the exquisite susceptibility of SJL/J mice to EAE. As PLP expression in the human thymus is also restricted to the DM20 isoform, these findings have implications for selection of the autoimmune T-cell repertoire in multiple sclerosis.